The Power of the Steel-tipped Pen : Reconstructing Native Hawaiian Intellectual History - Silva, Noenoe K., 1954- (Book collections on Project MUSE., 2017)
Noenoe K. Silva creates a model indigenous intellectual history of a culture where--using Western standards--none is presumed to exist by examining the work of two lesser-known Hawaiian language writers from the nineteenth-century whose prolific output across many genres created a record of Native Hawaiian cultural history and thought.